PUITIKA DALAM LIRIK SALUANG: Sebuah Kajian Etnolinguistik Minangkabau - Yanti Riswara (Madah: Jurnal Bahasa dan Sastra, 2012)
This paper is aimed at describing of how a culture relates to its community. Culture and community are two aspects that are not integral but interconnected each other. Every community must have a certain culture as inherent traits that mark a particular group. Culture can be used as a mirror to look at the characteristics of these groups . One element that can reflect the culture of a community is the lyrics of traditional songs; a kind of  traditional poems. The lyrics of the traditional songs can reflect  some social characters of the community of where the culture is attached. This study is a kind of qualitative research which applies a listening method of analysis by using ethnolinguistics approach.  The object of the analysis is the poetic lyrics of  a traditional song that is usually sang with tradisional music “s aluang”. The results of the analysis shows that some parts of Minangkabau characteristics are reflected in the poetic words used in the lyrics of “saluang”, such as the way of how Minangkabau people socially relating with families and with other community members. In  other words, it can be said that a poetic lyric of a traditional song is the reflection of it’s community.  Makalah ini bertujuan untuk menjelaskan bagaimana sebuah kebudayaan terhubung dengan masyarakatnya. Masyarakat dan budaya itu seperti dua sisi mata uang yang saling melengkapi satu sama lainnya. Setiap masyarakat memil iki budaya tersendiri yang menandai kelompoknya. Budaya dapat menjadi cerminan dari masyarakatnya, yang dapat dilihat dari sebuah produk budaya seperti lirik lagu tradisional, sebuah bentuk puisi tradisional. Lirik lagu tradisional sebuah kelompok masyarak at dapat merefleksikan beberapa karakter budaya masyarakat tersebut. Penelitian ini merupakan penelitian kualitatif dengan menerapkan metode simak dan pendekatan teori etnolinguistik. Objek penelitian adalah lirik-lirik puitis sebuah lagu tradisional Minangkabau yang biasa diiringi dengan alat musik saluang. Hasil kajian ini menunjukkan bahwa  beberapa karakter orang Minangkabau dapat dilihat dari lirik -lirik puitis saluang, misalnya bagaimana orang Minangkabau berinteraksi secara sosial dengan keluarga dan dengan anggota masyarakat lainnya. Dengan kata lain, lirik -lirik lagu tradisional dalam saluang dapat menggambarkan masyarakat pemiliknya.